Alteration of Endothelin 1, MCP-1 and Chromogranin A in patients with atrial fibrillation undergoing pulmonary vein isolation. - K Lackermair; S Clauss; T Voigt; I Klier; C Summo; B Hildebrand; T Nickel; H L Estner; S Kääb; R Wakili; U Wilbert-Lampen (PLoS ONE)
Background The relation between arrhythmias and stress is known. The aim of our current study was to elucidate whether plasma levels of previously described stress parameters are altered in highly symptomatic patients with atrial fibrillation (AF) per se and in patients undergoing ablation therapy by pulmonary vein isolation (PVI). Methods 96 patients with AF undergoing PVI were recruited. Plasma levels of Endothelin-1 (ET-1), MCP-1 and Chromogranin-A (CGA) were measured before and three months after ablation completed with clinical follow-up with respect to AF recurrence. Additionally, we examined 40 healthy age- and sex-matched volunteers as a reference. Results Symptomatic AF patients showed increased levels of ET-1 compared to healthy controls (2.62pg/ml vs. 1.57pg/ml; p<0.01). Baseline levels of ET-1 were higher in patients presenting with AF after PVI (2.96pg/ml vs. 2.57pg/ml;p = 0.02). The temporal comparison revealed decreased ET-1 levels in patients without (2.57pg/ml vs. 2.33pg/ml; p<0.01) and unchanged ET-1 levels in patients with AF after PVI. Baseline MCP-1 was increased in AF patients vs. controls (268pg/ml vs. 227 pg/ml; p = 0.03). Both groups, with and without AF after PVI, showed an increase of MCP-1 compared to baseline (268pg/ml vs. 349pg/ml;p<0.01; 281pg/ml vs. 355pg/ml;p = 0.03). CGA was lower in AF patients compared to healthy controls (13.8ng/ml vs. 25.6ng/ml;p<0.01). Over time patients without AF after PVI showed an increase of CGA (14.2ng/ml vs. 20.7ng/ml;p<0.01). No change was observed in patients with AF after PVI. Conclusion Our study demonstrated dysregulated levels of ET-1, MCP-1 and CGA in symptomatic AF patients. We could demonstrate an association between ET-1 to presence or absence of AF. Furthermore, we could show that a decrease of ET-1 as well as an increase of CGA after PVI, representing a trend towards control cohort levels, were both associated with restoration of sinus rhythm. These results provide new insights into the role of stress-related biomarkers in AF and AF treatment by ablation therapy.